Decontamination of Surfaces Exposed to Carbon-Based Nanotubes and Nanomaterials. (16th January 2014) - Su, Paul; Haghpanah, Babak; Doerr, William W.; Karimi, Zahra; Hassan, Syed; Gritzo, Louis; Busnaina, Ahmed A.; Vaziri, Ashkan
Abstract : Contamination of surfaces by nanomaterials can happen due to accidental spillage and release or gradual accumulation during processing or handling. Considering the increasingly wide use of nanomaterials in industry and research labs and also taking into account the diversity of physical and chemical properties of different nanomaterials (such as solubility, aggregation/agglomeration, and surface reactivity), there is a pressing need to define reliable nanomaterial-specific decontamination guidelines. In this paper, we propose and investigate a potential method for surface decontamination of carbon-based nanomaterials using solvent cleaning and wipes. The results show that the removal efficiency for single- and multiwalled carbon nanotubes from silicon wafers sprayed with water-surfactant solutions prior to mechanical wiping is greater than 90% and 95%, respectively. The need for further studies to understand the mechanisms of nanomaterial removal from surfaces and development of standard techniques for surface decontamination of nanomaterials is highlighted.